2020
DOI: 10.1177/0734282920930542
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Invariance in the Taiwan Wechsler Intelligence Scale for Children, Fifth Edition: Higher Order Five-Factor Model

Abstract: This study investigated the factorial invariance of the Taiwan Wechsler Intelligence Scale for Children, Fifth Edition (WISC-V) across age and gender. A higher order five-factor model was tested on a nationally representative sample of 1,034 children aged 6–16 years. The results demonstrated full factorial invariance for Taiwan children of different ages and gender. The WISC-V subtests demonstrated the same underlying theoretical latent constructs, strength of relations among factors and subtests, val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 48 publications
(65 reference statements)
4
16
1
Order By: Relevance
“…An evaluation of the strong (scalar) specification suggested that both sex and diagnostic groups attained full scalar invariance, while age-groups attained partial scalar invariance. The finding of full or partial scalar invariance was consistent with previous research findings with the extended WISC-V 16 primary and secondary subtest battery (e.g., Chen et al, 2020; Pauls et al, 2019; Reynolds & Keith, 2017; Scheiber, 2016) and other intelligence tests including the Kaufman assessment battery for children, second edition (Reynolds, Scheiber, Hajovsky, Schwartz, & Kaufman, 2015; Scheiber, 2017), Woodcock-Johnson (Edwards & Oakland, 2006; Keith, 1999), and differential ability scale (Keith, Quirk, Schartzer, & Elliott, 1999). However, this is the first study to investigate invariance of the WISC-V 10-primary subtest battery across several groups (e.g., sex, age, and clinical diagnosis) with a referred sample more than double the size of the normative sample.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…An evaluation of the strong (scalar) specification suggested that both sex and diagnostic groups attained full scalar invariance, while age-groups attained partial scalar invariance. The finding of full or partial scalar invariance was consistent with previous research findings with the extended WISC-V 16 primary and secondary subtest battery (e.g., Chen et al, 2020; Pauls et al, 2019; Reynolds & Keith, 2017; Scheiber, 2016) and other intelligence tests including the Kaufman assessment battery for children, second edition (Reynolds, Scheiber, Hajovsky, Schwartz, & Kaufman, 2015; Scheiber, 2017), Woodcock-Johnson (Edwards & Oakland, 2006; Keith, 1999), and differential ability scale (Keith, Quirk, Schartzer, & Elliott, 1999). However, this is the first study to investigate invariance of the WISC-V 10-primary subtest battery across several groups (e.g., sex, age, and clinical diagnosis) with a referred sample more than double the size of the normative sample.…”
Section: Discussionsupporting
confidence: 90%
“…This conclusion is particularly important for the clinical comparison group. There have been recent calls for structural validity and invariance analyses within clinical groups (Chen et al, 2020; Graves et al, 2020), but rarely are data sets such as the one in the present study available. In this case, although three distinctly different clinical groups were available—an externalizing disorder (i.e., ADHD), an internalizing disorder (i.e., anxiety), and a neurologically based disorder (i.e., encephalopathy)—the scoring structure was either fully or partially invariant and functions the same way regardless of sex, age, or clinical group.…”
Section: Conclusion and Implications For Practicementioning
confidence: 98%
See 3 more Smart Citations